Customer responses to CSR in the Pakistani banking industry. Issue 4 (1st June 2015) - Khan, Zia; Ferguson, David; Pérez, Andrea
Abstract : Purpose: – The purpose of this paper is twofold: to empirically analyse how customer corporate social responsibility (CSR) perceptions impact on the perceived service quality (PSQ)-loyalty relationship in the banking industry of Pakistan; and to evaluate the mediating role of customer trust in that model. Design/methodology/approach: – Based on a field survey of 408 customers of five different banks of Pakistan, the hypothesized model is tested through partial least squares based structural equation modelling. Findings: – The findings demonstrate that banking customers in Pakistan recognise CSR as a multidimensional construct that serves as a direct determinant of PSQ, trust, repurchase and word of mouth (WOM) intentions. PSQ also influences customer trust directly and positively and trust has a direct and positive impact on repurchase and WOM intentions. On the contrary, PSQ does not influence repurchase and WOM intentions directly. Its effect is mediated by customer trust. Practical implications: – Contrary to the previous mixed findings reported in the literature, this research confirms the explicit contribution of CSR towards customer perceptions and intentions in the context of the banking industry. The findings suggest that banking companies should take great care over preparing their CSR initiatives and include them in their marketing plans in order to improve customer loyalty intentions. In this way, CSR can enhance PSQ and customer trust, which are two key constructs in the loyalty model proposed in this paper. Originality/value: – The originality of the paper lies in the context in which the research was developed. The banking industry of Pakistan had not previously been extensively researched. The proposal for a comprehensive model that evaluates the role of customer trust is another key contribution of the paper. Previous research has not extensively studied the role of trust in loyalty models that evaluate CSR perceptions along with PSQ.